Inhibition of brain retinoic acid catabolism: a mechanism for minocycline's pleiotropic actions?. (16th November 2016) - Regen, F.; Le Bret, N.; Hildebrand, M.; Herzog, I.; Heuser, I.; Hellmann-Regen, J.
Abstract : Objectives. Minocycline is a tetracycline antibiotic increasingly recognized in psychiatry for its pleiotropic anti-inflammatory and neuroprotective potential. While underlying mechanisms are still incompletely understood, several lines of evidence suggest a relevant functional overlap with retinoic acid (RA), a highly potent small molecule exhibiting a great variety of anti-inflammatory and neuroprotective properties in the adult central nervous system (CNS). RA homeostasis in the adult CNS is tightly controlled through local RA synthesis and cytochrome P450 (CYP450)-mediated inactivation of RA. Here, we hypothesized that minocycline may directly affect RA homeostasis in the CNS via altering local RA degradation. Methods. We used in vitro RA metabolism assays with metabolically competent synaptosomal preparations from murine brain and human SH-SY5Y neuronal cells as well as viable human SH-SY5Y neuroblastoma cell cultures. Results. We revealed that minocycline potently blocks RA degradation as measured by reversed-phase high-performance liquid chromatography and in a viable RA reporter cell line, even at low micromolar levels of minocycline. Conclusions. Our findings provide evidence for enhanced RA signalling to be involved in minocycline's pleiotropic mode of action in the CNS. This novel mode of action of minocycline may help in developing more specific and effective strategies in the treatment of neuroinflammatory or neurodegenerative disorders.